Effect of the early stationary rehabilitation stage on prognosis in patients with type 2 diabetes mellitus who were exposed to acute coronary syndrome - E. A. Nikitina; E. N. Chicherina; O. S. Elsukova (Лечащий Врач, 2021)
The effectiveness of the second stage of cardiac rehabilitation on the prognosis in patients with type 2 diabetes mellitus (T2DM) and acute coronary syndrome (ACS) was evaluated. Based on our data, the lack of referral to the second stage of cardiac rehabilitation has no negative effect on the prognosis (death rate, myocardial infarction and myocardial revascularization during 12 months of observation) in patients with T2DM and ACS who did and did not undergo coronary intervention (percutaneous coronary intervention or bypass surgery).